Unionism 4.0? The organization of platform workers in Argentina - Diana Menéndez, Nicolás; Arias, Cora Cecilia; Haidar, Julieta (Sociología del Trabajo, 2020)
This article presents the results of a study conducted in Argentina during 2018 and 2019. The study engages in the debates around the possibilities for collective organization of platform workers. In particular it analyzes the characteristics of the labour process on delivery platforms in the city of Buenos Aires: Rappi, Glovo, and PedidosYa. In addition, is describes the specific features of the Argentinian union model and on the basis of different dimensions of analysis, two traditions that have characterized Argentinian unionism are constructed schematically.In the light of these union traditions, we analyze the actions developed by the two unions representing the interests of riders: ASIMM, the pre-existing union that represents couriers, and APP, a union set up to specifically defend platform workers.
Keywords: Argentina; Platform Companies; Unions; Workers; Delivery Platforms; Collective Organization; Union Traditions